Situation of menstrual management facilities in schools of peri-urban areas of Nepal: WASH, privacy, and healthcare. (12th November 2021) - Shrestha, Sadhana; Shrestha, Salina; Ito, Yuri; Kobayashi, Yuka; Nishida, Kei; Futaba, Kazama; Malla, Rabin
Abstract: Menstrual management (MM) facilities in schools are neglected in low- and middle-income countries. We examined the existing MM facilities, identified the deficient, and collected students' ideas in peri-urban schools of Nepal. The schools had basic MM facilities including water sanitation and hygiene (WASH) infrastructures, gender-segregated toilet facilities with taps, dustbins and running water, provision of emergency sanitary pads, etc. Out of 71 students who reported soiling of dresses with menstrual blood as a common problem, 27% went home and did not return in such situation instead of washing off at school. Forty-six per cent of students used washable absorbents, but washing and drying facilities were lacking, and students adapted by using disposable pads at school and washable at home. Out of 126 students, 106 took days off during menstruation in the past three months with an average of 2.6 days by one student. Sixty-one per cent gave the reason as pain and 39% tiredness for taking days off. Healthcare facilities were lacking in schools, hence, lack of these facilities in schools might be contributing to absenteeism. The traditionally advocated list of MM facilities for schools, largely involving WASH facilities, should be updated, including newly identified factors which were also suggested by students. HIGHLIGHTS: WASH infrastructures were available, but water supply and soap were less frequently managed. Reusable pads were advocated but lack of washing and drying space in schools made it less applicable Students developed coping strategy to use disposable pads at school and washables at home. A student skipped 2.6 school days in 3 months during menstruation due to health problems, but healthcare facilities were lacking.